Compound mutations in BCR-ABL1 are not major drivers of primary or secondary resistance to ponatinib in CP-CML patients - Deininger, Michael Werner Nikolaus; Müller, Martin Christian (Blood, 2016)
BCR-ABL1 kinase domain mutations can confer resistance to first- and second-generation tyrosine kinase inhibitors (TKIs) in chronic myeloid leukemia (CML). In preclinical studies, clinically achievable concentrations of the third-generation BCR-ABL1 TKI ponatinib inhibit T315I and all other single BCR-ABL1 mutants except T315M, which generates a single amino acid exchange, but requires 2 sequential nucleotide exchanges. In addition, certain compound mutants (containing ≥2 mutations in cis) confer resistance. Initial analyses based largely on conventional Sanger sequencing (SS) have suggested that the preclinical relationship between BCR-ABL1 mutation status and ponatinib efficacy is generally recapitulated in patients receiving therapy. Thus far, however, such analyses have been limited by the inability of SS to definitively identify compound mutations or mutations representing less than ∼20% of total alleles (referred to as “low-level mutations”), as well as limited patient follow-up. Here we used next-generation sequencing (NGS) to define the baseline BCR-ABL1 mutation status of 267 heavily pretreated chronic phase (CP)-CML patients from the PACE trial, and used SS to identify clonally dominant mutants that may have developed on ponatinib therapy (30.1 months median follow-up). Durable cytogenetic and molecular responses were observed irrespective of baseline mutation status and included patients with compound mutations. No single or compound mutation was identified that consistently conferred primary and/or secondary resistance to ponatinib in CP-CML patients. Ponatinib is effective in CP-CML irrespective of baseline mutation status.